Maternal mobility across the rural-urban divide: empirical data from coastal Kenya. - Molyneux, C; Mung'ala-Odera, V; Harpham, T; Snow, R (2002)
This paper describes the mobility patterns, rural-urban linkages and household structures for a low-income neighbourhood on the outskirts of Mombasa, Kenya's main port, and a rural settlement 60 kilometres away. Drawing on interviews with a sample of mothers resident in each location, it documents their perceptions of the advantages and disadvantages of rural and urban life, and shows the continuous interchange between the two areas. It also highlights how most rural to urban migrants are familiar with urban environments before moving and how, having moved, many maintain strong rural ties. The ways in which households are split across rural and urban areas is influenced by intra-household relations and by household efforts to balance the income-earning opportunities in town, the relatively low cost of living in rural areas and future family security. This produces dramatic differences between and among rural and urban mothers and suggests a need for policy makers and planners to recognize diversity and to build upon complex livelihood strategies that span the rural-urban divide.